Analysis of plasma assisted combustion under rich-fuel conditions - Roberto Aliandro Varella (2015)
The recently increasing interest in plasma assisted combustion is motivated by new possibilities for ignition and flame stabilization, in addition to pollutant emission reduction and control. The plasma generates a chemical active environment producing radicals, excited species and ions thus increasing the combustion process reaction rate. In this work the effect of plasma assisted combustion phenomena in a premixed flame of natural gas-air is investigated by using pollutant emission gas analysis, optical emission spectroscopy and high speed imaging. The plasma is created by using a gliding-arc discharge, chosen because of its properties: works at atmospheric pressure, generates high electron density plasma and has chemical selectivity. The reactor geometry limits the equivalence ratio (?) range of stability between ? = 0.3 - 0.7 and ? = 1.2 - 1.4. Within these ranges the equivalence ratios of ? = 1.2 and ? = 1.4 were chosen for investigation. The variable in this study is the applied electrical power ranging between 220W and 370W. Results show the behavior from fundamental components of natural gas combustion, as CH4, nitrous oxide components, carbon monoxide, carbon dioxide and others. Also, the formation of radicals was evaluated and high speed images were recorded for a better overview of the process. It was seen that relations between gas temperature, input electrical power and chemical dynamics influence the parameters of combustion, emission gases and radicals.